Development of LKPD through Cognitive Conflict Strategy Learning Assisted with Augmented Reality to Improve Mathematical Problem Solving Capability - Rusmini Rusmini; Elmanani Simamora; Mulyono Mulyono; Dian Armanto; Muktar Muktar (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This research aims to analyzing the validity, practicality and effectiveness of students' worksheets through cognitive conflict strategies to improve mathematical problem-solving abilities through learning cognitive conflict strategies assisted by Augmented Reality. The Ploomp model was used in this study. The subjects in this research are students in class VIII of SMP Negeri 4 Percut Sei Tuan. The research results showed that the student worksheet developed met the valid criteria based on an average score of 4.02, the practical student worksheet based on learning implementation IO =4.21 (high). The student worksheets developed have met the effective criteria in terms of classical completeness reaching 82.70%, student responses obtained above 80% for all students, namely 92%, increased problem- solving abilities seen from the average N-Gain value of trial of 0.30 increased to 0.60 in trial II, indicating that it was in the "medium" category. For the next implementation, it will be applied to several state junior high schools in Percut Sei Tuan District and analyze differences in mathematical problem-solving abilities seen from the school ranking, namely the accreditation of the state junior high school.